Do habituation, host traits and seasonality have an impact on protist and helminth infections of wild western lowland gorillas? - Pafčo, Barbora; Benavides, Julio A; Pšenková-Profousová, Ilona; Modrý, David; Červená, Barbora; Shutt, Kathryn A; Hasegawa, Hideo; Fuh, Terence; Todd, Angelique F; Petrželková, Klára J (Parasitology research, 2017)
Increased anthropogenic activity can result in parasite exchanges and/or general changes in parasite communities, imposing a health risk to great apes. We studied protist and helminth parasites of wild western lowland gorilla groups in different levels of habituation, alongside humans inhabiting Dzanga-Sangha Protected Areas in the Central African Republic. Faeces were collected yearly during November and December from 2007 to 2010 and monthly from November 2010 to October 2011. Protist and helminth infections were compared among gorilla groups habituated, under habituation and unhabituated, and the effect of host traits and seasonality was evaluated. Zoonotic potential of parasites found in humans was assessed. No significant differences in clinically important parasites among the groups in different stages of habituation were found, except for Entamoeba spp. However, humans were infected with four taxa which may overlap with taxa found in gorillas. Females were less infected with spirurids, and adults had higher intensities of infection of Mammomonogamus sp. We found seasonal differences in the prevalence of several parasite taxa, but most importantly, the intensity of infection of unidentified strongylids was higher in the dry season. This study highlights that habituation may not necessarily pose a greater risk of protist and helminth infections in gorilla groups.
Keywords: Animals; Gorilla gorilla; Female; feces; Feces; Seasons; Habituation; Western lowland gorilla; ženské pohlaví; Helminthiasis, Animal; lidé; Parasite; Středoafrická republika; roční období; Strongyloidea; Phylogeny; nemoci lidoopů; Ape Diseases; zvířata; Central African Republic; fylogeneze; helmintózy zvířat; Entamoeba; Human impact; Humans